2019
DOI: 10.3389/fpls.2018.01960
|View full text |Cite
|
Sign up to set email alerts
|

Clone-Dependent Expression of Esca Disease Revealed by Leaf Metabolite Analysis

Abstract: Grapevine trutk diseases, especially Esca, are of major concern since they gradually alter vineyards worldwide and cause heavy economic losses. The expression of Esca disease symptoms depends on several factors, including the grapevine cultivar. In this context, a possible clone-dependent expression of the Esca disease was studied. Two clones of ‘Chardonnay’ grown in the same plot were compared according to their developmental and physiological traits, metabolome, and foliar symptom expression. Analysis of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 37 publications
1
26
0
Order By: Relevance
“…Alvarino affected by esca [15] and could result from rerouting of sugars toward specialized metabolite synthesis. In contrast, Moret et al [18] found a higher level in carbohydrates such as glucose and fructose in leaves of Chardonnay clone 95 plants showing esca symptoms. In our study, decrease of sugars we observed in the wood could thus also be explained by remobilization toward the leaves to better sustain the infection.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Alvarino affected by esca [15] and could result from rerouting of sugars toward specialized metabolite synthesis. In contrast, Moret et al [18] found a higher level in carbohydrates such as glucose and fructose in leaves of Chardonnay clone 95 plants showing esca symptoms. In our study, decrease of sugars we observed in the wood could thus also be explained by remobilization toward the leaves to better sustain the infection.…”
Section: Discussionmentioning
confidence: 84%
“…Interaction between grapevine and trunk disease-associated fungi is also poorly understood, especially in the wood. Previous metabolomic studies of grapevine infected by trunk disease fungi were performed on leaves [15,18]. However, to gain a better understanding of mechanisms underlying trunk disease progression, there is a need to study metabolic perturbations in the wood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Literature data indicate that ESCA is a multi-factor disease, and many complex pathological scenarios could explain the emergence of symptoms. GLSD, characterized by tiger stripe-like symptoms on the leaves, is the most common expression of the disease [ 3 , 44 ]. ESCA-associated fungi are undetected in the distal organs of the vines (i.e., annual stems and leaves), demonstrating that vascular occlusions and symptoms occur at a distance from the pathogen niche localized in the wood [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…While no grapevine cultivar is known to be completely resistant to ESCA, degrees of susceptibility ranging from highly susceptible to tolerant have been reported [ 44 ]; however, the plant defense mechanisms underlying these observations have not been completely elucidated. Studies that have focused on identifying the host response to ESCA have found that the wood/foliar symptomatology described above is linked to characteristic adaptive physiological [ 38 ] and metabolic changes [ 36 ].…”
Section: Introductionmentioning
confidence: 99%